1994
DOI: 10.1007/bf02843606
|View full text |Cite
|
Sign up to set email alerts
|

Impact of television on children

Abstract: Television viewing has a great impact on various aspects of child's life. This study was carried out at Sir Padampat Mother & Child Health Institute, Jaipur (Rajasthan). The aim was to study the effects of television viewing on a child's eating habits, general physical health, physical activities, interest in study and school performance. Only 250 children of 3-10 years age groups were studied for a period of nine months (January 1992 to September 1992). Average duration of television exposure to an individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 6 publications
3
17
1
4
Order By: Relevance
“…Of these, nine were not included in the review because they involved experimental manipulations of sedentary behavior and physical activity, 40 involved interventions targeting additional sedentary behaviors, [41][42][43] were single-subject case studies, 44,45 measured only body mass, 46 or presented data previously published. 47 From the remaining 30 studies, data were available on 52 independent samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, nine were not included in the review because they involved experimental manipulations of sedentary behavior and physical activity, 40 involved interventions targeting additional sedentary behaviors, [41][42][43] were single-subject case studies, 44,45 measured only body mass, 46 or presented data previously published. 47 From the remaining 30 studies, data were available on 52 independent samples.…”
Section: Resultsmentioning
confidence: 99%
“…7 TV viewing, video/computer game use and physical activity In total, 33 studies [11][12][13]17,18,21,25,[30][31][32]36,38,39,46,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] were located that presented a measure of association between physical activity and TV viewing, playing video games or computer use. Nine studies were excluded from analyses either because they had serious design limitations, 46,50,51 presented insufficient data for meta-analytic synthesis, 11,12,54 presented data on composite measures of sedentary behavior 49,52 or reported on special populations. 36 The remaining [24] studies presented data on [41] independent samples (the unit of analysis) and were included in the final analyses.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…In their sample, watching TV or playing computer games after 20.00 h was also related to less sleep duration. Other studies found many adverse effects of television viewing on children such as sleep disorders (Johnson et al, 2004;Owens et al, 1999;Tynjala et al, 1993;van den Bulch, 2004) and poor sleep habits (Gupta et al, 1994). Cross-sectional studies found that television/videotape viewing was associated with late bedtimes and sleep disturbances among school-aged children and adolescents (Owens et al, 1999;Tynjala et al, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…Television-viewing habits have been reported to be associated with a variety of significant behavioral consequences, including obesity and poor eating habits (Locard et al 1992), decreased physical activity and physical fitness (Durant 1994), impaired academic performance (Gupta et al 1994), aggressive behavior (Gadow and Sprafkin 1989), and less opportunity for social interaction (Robinson 1972). Extensive television viewing habit has also been reported to be associated with increased restlessness and difficulty in falling or staying asleep (Owens et al 1999).…”
Section: Introductionmentioning
confidence: 99%